A common ground for pain and depression - Tappe-Theodor, Anke; Kuner, Rohini (Nature neuroscience, 2019)
Chronic pain is associated with anxio-depressive comorbidities, but the neuroanatomical substrates remain unknown. A specific serotonergic pathway from the dorsal raphe nucleus to the lateral habenula via the central amygdala is now uncovered as a key neural circuit governing comorbid depressive symptoms in chronic pain.